2018
DOI: 10.4238/gmr16039883
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic diversity among accessions of Capsicum annuum L. through morphoagronomic characters

Abstract: Genetic variability among pepper genotypes is essential in obtaining hybrid combinations with greater heterotic effect and in obtaining superior strains. This work's goal was to evaluate the genetic diversity between accessions of Capsicum annuum L., indicating the selection of promising individuals for ornamental purposes. The experiment was carried out in at the Plant Biotechnology Laboratory of the Center of Agricultural Sciences, Federal University of Paraíba. The experiment was conducted in a completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
2
11
0
2
Order By: Relevance
“…High values of heritability are extremely important for the accuracy in the selection of genotypes based on the evaluated characteristics. Similar results to those demonstrated in the present study were reported by Pessoa et al (2018).…”
Section: /7supporting
confidence: 94%
“…High values of heritability are extremely important for the accuracy in the selection of genotypes based on the evaluated characteristics. Similar results to those demonstrated in the present study were reported by Pessoa et al (2018).…”
Section: /7supporting
confidence: 94%
“…Buah merupakan salah satu bagian tanaman yang menjadi Keterangan : angka yang diikuti huruf yang sama pada kolom yang sama menunjukkan hasil yang tidak berberda nyata menurut uji DMRT 5%. (Santos Pessoa et al, 2018).…”
Section: Bobot Buah Panjang Buah Panjang Tangkai Buah Dan Diameterunclassified
“…Therefore, they should exhibit some remarkable morphological characteristics that support their aesthetic value, such as small, erect, and colorful fruits that present a color contrast with the foliage over the whole ripening process. Other positive features would include: vivid foliage, easiness to grow, long durability and the possibility of being grown in small pots [ 29 , 30 , 31 ]. The subsequent search for new shapes and colors as well as new flavors when used as food encouraged their cultivation and commercialization.…”
Section: Introductionmentioning
confidence: 99%